Biobanking and Cryopreservation of Stem Cells - Karimi-Busheri, Feridoun; Weinfeld, Michael (Advances in Experimental Medicine and Biology,, 2016)
Biobanking is considered to be one of the ten ideas changing the world with an estimated value of $45 billion by 2025. Despite the challenges, as the climate for innovation in the biobanking industry continues to flourish around the world, it is certain that amazing discoveries will emerge from this large-scale method of preserving and accessing human samples; biobanking is no longer just a place for collecting and storing samples. This book will cover a wide variety of subjects from across the future biobanking spectrum including scientific strategies, personalized medicine, regenerative medicine and stem cell challenges, disease surveillance, population genetics and innovative methods of biobanking.